Analisis Sistem Distribusi Air Bersih di Komplek Perumahan Cemara Hijau Medan - Ikhwan Fauzi Nasution; Ivan Indrawan; Muhammad Faisal (Universitas Andalas, 2018)
Cemara Hijau Housing Complex is an elite housing complex located on the outskirts of Medan which each year has an increasing number of consumers not followed by increased network capacity and clean water supply. This study aims to analyze the pattern of water consumption of customers in the Green Pine complex, analyzing the availability of PDAM Tirtanadi water of Cemara branches with water needs of Cemara Hijau customers and analyzing the clean water distribution system in Cemara Hijau housing using Hardy Cross method with Hazen William and Epanet 2.0 equations. The research method used is to first conduct literature studies related to clean water distribution system and Epanet 2.0 application. Then collect the required data that is primary data and secondary data. Then the data data is analyzed by manual calculation of Hardy Cross with Hazen William equation and using computer software that is Epanet 2.0. The result of research is the pattern of clean water consumption in the green pine complex with the highest factor is 1.69 while the lowest is 0.21, then the water loss at the Cemara Hijau Housing Complex is 52.93%, then the clean water distribution network system in the Cemara Hijau Housing Complex does not meet in terms of flow and pressure, so that the solution given is the addition of 50 mm diameter made in parallel, the last of the total difference obtained from Epanet 2.0 with a large enough field for the hourly of 0.0766 m3/sec and for 24 hours of 4.3878 m3/sec, and the total difference between Epanet 2.0 with Hardy Cross method with Hazen William equation is not too large with a total difference of 0.00048 m3/sec or 0.48 liter/sec.